Uji Efektivitas Repellent Sediaan Lotion Kombinasi Minyak Atsiri Daun Zodia (Evodia suaveolens Scheff) dan Minyak Atsiri Batang Serai (Cymbopogon citratus) Terhadap Nyamuk Aedes aegypti L. - Puput Mirawati; Eva Susanty Simaremare; Rani Dewi Pratiwi (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2018)
Zodia (Evodia suaveolens Scheff) and lemongrass (Cymbopogon citratus) are native Indonesian plants with repellant activity against mosquitoes and insects. The purpose of this research were to formulate and evaluate the repellant activity of zodia-serai lotion against Aedes aegypti and determine the protection power of three formulas of lotion. The method used in this research including steam distillation of essential oil from zodia leaves and lemongrass, formulation and evaluation of lotions, power protection test, and data analysis. The result of this research showed that lotion had acidic pH of 5, and they were stable without separation after stability evaluation with centrifugation. The most effective repellant activity of the lotion was exhibited at 0 hours with 100% of repellency. The best combination of essential oils of zodia (Evodia suaveolens Scheff) and lemongrass (Cymbopogon citratus) as Aedes aegypti repellent was at ratio of 7:3.